The analysis of morphometric data on rocky mountain wolves and artic wolves using statistical method - Shafi, Muhammad Ammar; Rusiman, Mohd Saifullah; Amir Hamzah, Nor Shamsidah; Nor, Maria Elena; Ahmad, Noor'ani; Mohamad Azmi, Nur Azia Hazida; Ab Latip, Muhammad Faez; Azman, Ahmad Hilmi (2018)
Morphometrics is a quantitative analysis depending on the shape and size of several specimens. Morphometric quantitative analyses are commonly used to analyse fossil record, shape and size of specimens and others. The aim of the study is to find the differences between rocky mountain wolves and arctic wolves based on gender. The sample utilised secondary data which included seven variables as independent variables and two dependent variables. Statistical modelling was used in the analysis such was the analysis of variance (ANOVA) and multivariate analysis of variance (MANOVA). The results showed there exist differentiating results between arctic wolves and rocky mountain wolves based on independent factors and gender.